URB597 protects against NLRP3 inflammasome activation by inhibiting autophagy dysfunction in a rat model of chronic cerebral hypoperfusion - Su, Shao-Hua; Wu, Yi-Fang; Lin, Qi; Wang, Da-Peng; Hai, Jian (Journal of neuroinflammation, 2019)
Previous studies reported that URB597 (URB) had therapeutic potential for treating chronic cerebral hypoperfusion (CCH)-induced neuroinflammation and autophagy dysfunction. However, the interaction mechanisms underlying the CCH-induced abnormal excessive autophagy and neuroinflammation remain unknown. In this study, we investigated the roles of impaired autophagy in nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing (NLRP) 3 inflammasome activation in the rat hippocampus and the underlying mechanisms under the condition of induced CCH as well as the effect of URB treatment. The CCH rat model was established by bilateral common carotid artery occlusion (BCCAo), and rats were randomly divided into 11 groups as follows: (1) sham-operated, (2) BCCAo; (3) BCCAo+autophagy inhibitor 3-methyladenine (3-MA), (4) BCCAo+lysosome inhibitor chloroquine (CQ), (5) BCCAo+microglial activation inhibitor minocycline, (6) BCCAo+ROS scavenger N-acetylcysteine (NAC), (7) BCCAo+URB, (8) BCCAo+URB+3-MA, (9) BCCAo+URB+CQ, (10) BCCAo+URB+minocycline, (11) BCCAo+URB+NAC. The cell localizations of LC3, p62, LAMP1, TOM20 and NLRP3 were assessed by immunofluorescence staining. The levels of autophagy-related proteins (LC3, p62, LAMP1, BNIP3 and parkin), NLRP3 inflammasome-related proteins (NLRP3, CASP1 and IL-1β), microglial marker (OX-42) and proinflammatory cytokines (iNOS and COX-2) were evaluated by western blotting, and proinflammatory cytokines (IL-1β and TNF-a) were determined by ELISA. Reactive oxygen species (ROS) were assessed by dihydroethidium staining. The mitochondrial ultrastructural changes were examined by electron microscopy. CCH induced microglial overactivation and ROS accumulation, promoting the activation of the NLRP3 inflammasome and the release of IL-1β. Blocked autophagy and mitophagy flux enhanced the activation of the NLRP3-CASP1 inflammasome pathway. However, URB alleviated impaired autophagy and mitophagy by decreasing mitochondrial ROS and microglial overactivation as well as restoring lysosomal function, which would further inhibit the activation of the NLRP3-CASP1 inflammasome pathway. These findings extended previous studies indicating the function of URB in the mitigation of chronic ischemic injury of the brain.